Comparison of microstructure, toughness, mechanical properties and work hardening of titanium/TiO2 and titanium/SiC composites manufactured by accumulative roll bonding (ARB) process. Issue 10 (July 2017) - Moradgholi, J.; Monshi, A.; Farmanesh, K.; Toroghinejad, M.R.; Loghman-Estarki, M.R.
Abstract: In this study, the effects of TiO2 ceramic nanoparticles and SiC microparticles on the microstructure, mechanical properties and toughness of titanium/TiO2 nanocomposite and titanium/SiC composite were investigated. To achieve this goal, TiO2 and SiC ceramic particles were incorporated as the reinforcement in titanium through the ARB (accumulative roll bonding) process. By adding SiC ceramic particles, the mechanical properties of the composite and the nanocomposite were enhanced, while their toughness was decreased, as compared to TiO2 nanoparticles. After applying 8 cycles of the ARB process, UTS in Ti/5 vol% SiC composite reached to about 1200 (MPa), as compared to that in Ti/0.5 wt% TiO2 nanocomposite, which was about 1100 (MPa). Furthermore, toughness in the Ti/5 vol% SiC composite and the Ti/0.5 wt% TiO2 nanocomposite was 60 and 29 J/m 3, respectively. Finally, SEM and TEM images showed SiC microparticles clustering in Ti/SiC composite samples and a suitable distribution of TiO2 nanoparticles in the Ti/TiO2 nanocomposite. By adding TiO2 nanoparticles, mechanical properties and work hardening coefficient were found to be increased, as compared to those of the monolithic samples. TiO2 nanoparticles, after being distributed in the titanium matrix through the ARB process, caused pin dislocations. As clearly shown in TEM images, dislocation tangles around TiO2 nanoparticles acted as the main mechanism improving the work hardening coefficient.